Cultivating a Secure Digital Future: The Nexus of Innovation and Data Protection in Modern Organizations - Shi, Jianzheng (Eximia, 2023)
In the digital era, the interconnectivity between producers and consumers has evolved, presenting both opportunities and challenges. This article delves into the role of fostering innovation behavior in organizations, emphasizing its significance in data protection and the cultivation of a technology security culture. Introducing the "Data Tradeoff Framework", the article provides a comprehensive perspective on big data application scenarios, highlighting the importance of understanding data’s intrinsic characteristics. With the rise of Fintech in regions like China and Southeast Asia, questions about data ownership, privacy, and competitive dynamics have become paramount. The article argues that while data has the potential to influence market dynamics, its responsible use can lead to a vibrant competitive landscape, promoting innovation and safeguarding consumer interests. The overarching message is the necessity for organizations to adopt a holistic approach to data, ensuring protection, transparency, and innovation in tandem.